Pelatihan Video Editing Sebagai Sarana Kreativitas Dan Peningkatan Ekonomi Digital Masyarakat - Rudi Kurniawan; Ryan Hamonangan; Ahmad Muhaimin; Ahmad Rai Fatkaozi (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In today’s digital era, video editing skills have become essential competencies to support creativity and open up economic opportunities, especially for grassroots communities. This community service program aims to empower the public through video editing training as a means of creative development and enhancing participation in the digital economy. The training focuses on the introduction of popular editing software, basic cutting techniques, transitions, adding visual and audio effects, and creating content for social media and small business promotion. Through hands-on practice, participants are trained to independently produce creative videos and are encouraged to understand monetization opportunities through platforms such as YouTube, TikTok, or freelance services like Fiverr and Upwork. The training resulted in significant improvements in participants' technical skills and increased confidence in creating digital content. Some participants have even started new economic activities based on their newly acquired editing skills. The program also encouraged the formation of a digital creative community as a platform for sharing experiences, job opportunities, and collaborative content projects. Additionally, program sustainability is supported through post-training mentoring and self-learning materials. Overall, this training presents a practical solution for communities to enhance their competitiveness in the ever-growing creative and digital economy sector.